Thermal fluctuations independently modulate physiological plasticity and the dynamics of the gut microbiome in a tropical rocky shore oyster - Bovern Suchart Arromrak; Adrian Tsz Chun Wong; Tin Yan Hui; Kin Sum Leung; Gray A. Williams; Monthon Ganmanee; Thierry Durand; Jetty Chung Yung Lee; Juan D. Gaitan-Espitia (My University, 2023)
Abstract Extreme high thermal conditions on tropical rocky shores are challenging to the survival of intertidal ectotherms. Yet, many species are highly successful in these environments in part due to their ability to regulate intrinsic mechanisms associated with physiological stress and their metabolic demand. More recently, there has been a growing awareness that other extrinsic mechanisms, such as animal-associated microbial communities, can also influence the tolerance and survival of ectotherms under stressful conditions. However, the extent to which the intrinsic and extrinsic mechanisms are functionally linked as part of the overall adaptive response of intertidal animals to temperature change and stress is poorly understood. Here, we examined the dynamics and potential interactions of intrinsic and extrinsic mechanisms in the tropical high-supratidal oyster, Isognomon nucleus . We found that oysters modulate their internal biochemistry (oxidized PUFA products, including 5-F 2t -IsoP, 10-F 4t -NeuroP, 13-F 4t -NeuroP, and 16-F 1t -PhytoP) as part of their adaptive regulation to cope with physiological stress during periods of extreme high temperatures when emersed. However, while we detected variation in alpha diversity (ASV richness and Shannon diversity index), dominant microbial taxa and microbial functions across time, no association was found with the host biochemical profiles. The findings here suggest that the thermal condition within oysters can independently influence their intrinsic biochemical responses and extrinsic microbiome profiles. Together, these mechanisms may contribute to the thermal tolerance and survival of the oysters in the challenging conditions of the tropical high-supratidal zone.
Keywords: Ectotherm; Extreme environment; Marine Bivalve and Aquaculture Studies